Preparation and characteristics of a novel rare earth borate K2O·CaO·4B2O3·12H2O:Ce3+. (1st November 2013) - Bi, Y; Tian, Y-W; Wang, G-S; Xiao, L-J
<x xml:space="preserve">Abstract</x> A new hydrated rare earth borate K2O·CaO·4B2O3·12H2O:Ce3+ has been synthesised by water solution method. The product is characterised by the XRD, IR, TG-DSC and SEM respectively and it is indicated that one single crystal has been obtained via spontaneous crystallisation. Under UV excitation, the luminescent property has also been investigated by F-4600 spectrophotometer.